Metabolite Profiling of Tabat Barito (Ficus deltoidea) Using UPLC-QTOF-MS/MS - Nurmaida Nurmaida; Latifah K Darusman; Mohamad Rafi; Rudi Heryanto (The Journal of Pure and Applied Chemistry Research, 2018)
Tabat Barito (Ficus deltoidea) is known as a plant that has potency as an antioxidant because of containing a significant phenolic compound. In this study, we performed metabolite profiling on F. deltoidea leaves by UPLC-QTOF-MS/MS to identify its phenolic compounds. Extraction by maceration and ultrasonication techniques with methanol (MM and UM) and ethanol (ME and UE) were used to extract the F. deltoidea metabolites. About 70 metabolites were identified by using UPLC-QTOF-MS/MS in negative ion mode. The amounts of metabolites found in each extract were different, i.e., 45 metabolites in MM, 64 metabolites in UM, 42 metabolites in UE and 41 metabolites in ME. MS/MS could further tentatively identify 16 metabolites. The identified compounds belonged to the class of flavonoids and phenolic acid. Also, we conducted an antioxidant activity by using DPPH method on each extract to determine its potency as an antioxidant. The highest antioxidant activity was exhibited by UM extract (IC50 71.93 ppm) may be due to the number of metabolites in UM extract which was higher than the other extract based on the detected metabolites.